Hubungan Indeks Massa Tubuh Diatas Normal Terhadap Premenstrual Syndrome Pada Wanita Usia Reproduktif Di Kelurahan Loa Ipuh Kabupaten Kutai Kartanegara - Rahman, Sandra Aulia; , dr. Retno Setyaningsih, Sp. PD; , dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background:Premenstrual Syndrome (PMS) is a group of physical and psychological symptomps which occurs before the time of menstruation. In general, the female premenstrual syndrome prevalence is about 90%, whereas 3- 5% of them experienced disturbance symptomps of daily life. One of the premenstrual syndrome's risk factors is Body Mass Index. Objective: To determine the relationship of Body Mass Index to premenstrual syndrome od reproductive women in Loa Ipuh Village Kutai Kartanegara District. Method: This study used observational analytic method with cross sectional design. Spearman test were used to examine the ignificance of the correlatin between two variables. The independent variable is Body Mass Index and the dependent variable is premenstrual syndrome. Subjects in this study were 86 samples. Results: 43 respondents who has BMI above the normal range, there was 25 respondents (29,0%) experienced PMS and 17 respondents (19,7%) didn't experience it. Whereas 43 respondents who has BMI in normal range, there was 5 respondents (5,8%) experienced PMS and 39 respondents (45,3%) didn't experience it. This research has p value = 0,000 and r value = 0,488 which means te results has significance correlation between Body Mass Index and remenstrual syndrome. Conclusion: Womans with Body Mass Index above the normal range has higher risk to experience premenstrual syndrome than woman with Body Mass Index in normal range.